Religion and Economy: How the Act of Rational Economy Dominates Muslim Entrepreneurs - Dede Nurohman; Evi Muafiah (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2021)
This research aimed to explore the motives that encouraged Muslim entrepreneurs to make business decisions in running businesses, and also to examined the effects of their religions as well as the business logics they used toward their trading behaviors. The subjects of this research were the Muslim entrepreneurs running the business of apparel convection in Botoran, Tulungagung. This research used qualitative method with phenomenological approach. The data extracting technique was conducted by documentation, observation, and interviews. The results showed that Muslim traders based their business behaviors on the consideration of rational choices. Such behaviors were manifested in the forms of: choosing to partition their houses as the place of production (home factory); choosing to procure capital through the Chinese; choosing temporary sewing workers; choosing to replace the procurement of computer embroidery machines; dun-dunan rego (decreasing the costs); nembak (lighting); and reluctant to establish a cooperative to accommodate them. Meanwhile, religion, morals, and other values are not considered by them in running their business. The implication of the findings is that religious and economic motives always appeared in a person's business processes. The dominance of one of them was determined by the environment and experience. Sharia financial institutions in the vicinity, such as Sharia Banks and BMT (Baitul Mal wa Tamwil, a sharia-based microfinance institution or cooperative), as well as Islamic organizations, with the right kinship approach, were required to be present to pay attention to business development and community empowerment.